Investment Policies in the Arab Countries : Papers Presented at a Seminar held in Kuwait, December 11-13, 1989 - El-Naggar, Said. (Washington, D.C. : International Monetary Fund, 1990)
This volume, edited by Said El-Naggar, examines the impact of macro- and microeconomic policies on the investment climate in the Arab countries, the efficiency of public investment, and the role of foreign direct investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet